Analisis keterampilan membaca dan menulis permulaan pada siswa kelas 1 sekolah dasar - Rina Prasetyaningsih; Jenny Indrastoeti Siti Poerwanti; Sularmi Sularmi (Universitas Sebelas Maret, 2022)
This study aims to describe the initial reading and writing skills possessed and the factors that influence by grade 1st students at SDN Jajar No. 73 Surakarta. The research method used is a descriptive qualitative research. Data were collected using observation, interview, test and documentation techniques. Data analysis techniques used are data reduction, data presentation, and data verification. The results show that students still often make mistakes in initial reading and writing. Errors in initial reading and writing that are often done are mispronunciation of vowels and consonants, inaccuracy in reading the syllables, inability to read simple words and sentences, difficulty in pronouncing words containing digraphs and diphthongs, reads simple sentences haltingly, uses irregular intonation, uses a voice that is not clear, difficulty in copying writing neatly, precisely, and completely, often making mistakes in writing sentences based on the objects seen, and writing sentences read by teacher incompletely. The skills are influenced by factors from inside and outside the students. The overall results of the study indicate the initial reading and writing skills of some students is still low. Therefore, the teachers can evaluate the use of appropriate learning methods and models to improve students' initial reading and writing skills.